Crystal Structure of Nanoscale Tin Dioxide Films Produced by Magnetron Sputtering - Sokol, Yevgen I.; Pirohov, O. V.; Klochko, N. P.; Novikov, V. A.; Khrypunov, G. S.; Klepikova, K. S. (Kyiv polytechnic institute, 2014)
Investigation of direct current magnetron sputtering parameters effects on the crystal structure of gas sensitive tin dioxide films has revealed that the change in the substrate temperature and in the film thickness leads to the transition from the condensation of metastable conglomerates of amorphous globules to the ≈15 nm SnO₂ crystallites with three-dimensional shape and well-defined edges. The dependence of the SnO₂ structure from the working Ar-O₂ gas mixtures and from their humidity evidences the significant role of the adsorption in the kinetics of the magnetron sputtering of tin dioxide. Due to the adsorption the morphological and dimensional characteristics of the tin dioxide films demonstrate the anomalous stability of the amorphous globules with their enhanced specific surface energy and the stabilization of the amorphous state, selectively retained even after the SnO₂ film reach in general the critical thickness of the crystallization.
Keywords: tin dioxide; crystal structure; gas sensor; electron microscopy